2006
DOI: 10.1523/jneurosci.0329-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Regulation of Synaptic GABA Release by the Glutamate-Glutamine Cycle in Hippocampal Area CA1

Abstract: Vesicular GABA and intraterminal glutamate concentrations are in equilibrium, suggesting inhibitory efficacy may depend on glutamate availability. Two main intraterminal glutamate sources are uptake by neuronal glutamate transporters and glutamine synthesized through the astrocytic glutamate-glutamine cycle. We examined the involvement of the glutamate-glutamine cycle in modulating GABAergic synaptic efficacy. In the absence of neuronal activity, disruption of the glutamate-glutamine cycle by blockade of neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
219
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(229 citation statements)
references
References 48 publications
7
219
2
1
Order By: Relevance
“…MSO has been widely used as a GS inhibitor in astroglia in studies of hyperammonemia, memory consolidation, and seizures, and its effects can be counteracted by glutamine application (Bacci et al, 2002;Suarez et al, 2002;Gibbs and Hertz, 2005;Tanigami et al, 2005;Liang et al, 2006). One recent study has used MSO to examine the effect of inflammatory stimuli on activation of GS in astroglia and found that GS activation is related to glutamatergic receptor activation (Muscoli et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSO has been widely used as a GS inhibitor in astroglia in studies of hyperammonemia, memory consolidation, and seizures, and its effects can be counteracted by glutamine application (Bacci et al, 2002;Suarez et al, 2002;Gibbs and Hertz, 2005;Tanigami et al, 2005;Liang et al, 2006). One recent study has used MSO to examine the effect of inflammatory stimuli on activation of GS in astroglia and found that GS activation is related to glutamatergic receptor activation (Muscoli et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This shuttle includes the uptake of excessive extrasynaptic glutamate and the production [via glutamine synthetase (GS)] and release from astroglia of glutamine, which is then taken up by neuronal elements to replenish the supply of glutamate (Zwingmann and Leibfritz, 2003;Hertz, 2004;Hertz and Zielke, 2004;Fonseca et al, 2005). A potent inhibitor of GS in astroglia is methionine sulfoximine (MSO), and its effects can be counteracted by glutamine application (Bacci et al, 2002;Blin et al, 2002;Suarez et al, 2002;Shin et al, 2003;Gibbs and Hertz, 2005;Tanigami et al, 2005;Liang et al, 2006). However, only one study has used MSO to investigate the involvement of astroglial GS in the effects of noxious stimuli on glutamatergic receptor-related events in astroglia (Muscoli et al, 2005), and no studies have tested its effects on central sensitization in functionally identified nociceptive neurons.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to influencing mTORC1 activity, glutamine is a precursor used in the synthesis of the neurotransmitters glutamate, aspartate, and GABA (Wang et al 2007;Albrecht et al 2010). It has been previously shown that glutamine can play an important role in regulating synaptic signaling, having impacts on both excitatory (Albrecht et al 2010;Uwechue et al 2012;Tani et al 2014) and inhibitory (Liang et al 2006;Wang et al 2007) synaptic signaling through its effects on glutamate and GABA synthesis and release. As shown in Figure 1, we did not observe any significant change in the overall hippocampal levels of glutamate or aspartate 30 min post-glutamine infusion, although changes in the synaptic levels of these neurotransmitters could not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the GABAergic synapses, the majority of this neurotransmitter is recycled in neurons, but part of the released GABA is taken up by surrounding astrocytes and therefore lost from the transmitter pool (Schousboe et al, 2013) . The latter event is compensated by glutamine acting to replenish the neurotransmitter pool of GABA (Liang et al, 2006;Patel et al, 2001;Schousboe, 2003).…”
Section: Introductionmentioning
confidence: 99%